(untitled) (gjstudies, 2015)
This research investigates the relationship between accounting information systems (AIS) and organizational reporting efficiency outcomes through a novel methodological lens that integrates principles from cybernetics and information theory.While prior studies have examined AIS impacts on decision-making or control, thispaper uniquely conceptualizes reporting efficiency as a dynamic, multi-dimensionalconstruct comprising temporal, qualitative, and resource utilization components.We develop and test a cybernetic feedback model that posits AIS not only processtransactions but also regulate reporting efficiency through adaptive feedback loopsinvolving data granularity, integration depth, and user-system interactivity. Employing a mixed-methods approach across three industry sectors—manufacturing,healthcare, and non-profit—we collect longitudinal data from 42 organizations overa 24-month period. Quantitative analysis utilizes a time-series cross-sectional designmeasuring efficiency metrics before and after AIS modifications, while qualitativecase studies explore the mechanisms underlying efficiency changes. Results reveala non-linear relationship between AIS sophistication and reporting efficiency, withdiminishing returns beyond optimal configuration thresholds. Notably, we identifya previously unreported ’information viscosity’ effect, wherein excessive data integration can impede efficiency by overloading feedback channels. The study alsodemonstrates that modular, interoperable AIS architectures yield superior efficiencyoutcomes compared to monolithic systems, particularly in volatile environments.These findings challenge conventional wisdom advocating for maximal system integration and complexity, offering instead a contingency framework for AIS designaligned with organizational cybernetic capacity. The research contributes originaltheoretical insights by applying control theory to accounting systems and providespractical guidance for configuring AIS to achieve sustainable reporting efficiencygains.